2021
DOI: 10.1021/acs.inorgchem.1c01604
|View full text |Cite
|
Sign up to set email alerts
|

On the Importance of Ligand-Centered Excited States in the Emission of Cyclometalated Ir(III) Complexes

Abstract: The photophysical behavior of the cyclometalating Ir(III) complexes [Ir(ppy) 2 (bpy)] + , where Hppy is 2-phenylpyridine and bpy is 2,2′-bipyridine (complex 1 ), and [Ir(diFppy) 2 (dtb-bpy)] + , where diFppy is 2-(2,4-difluorophenyl)pyridine and dtb-bpy is 4,4′-di- tert -butyl-2,2′-bipyridine (complex 2 ), has been theoretically investigated by perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…As revealed by photophysical experiments, complexes 2–4 show a similar deep blue emission, but their PLQYs in solution largely differ because of their largely different k nr values (Table ). Recent research work has revealed that the difference in the character of emissive triplet states can lead to largely different PLQYs for cationic Ir­(III) complexes with similar strucures . Here, complexes 1–4 all show an emission originating from 3 π–π* (C ∧ N-centered)/ 3 MLCT (Ir → C ∧ N) states, and therefore, the difference in the character of emissive triplet states is unlikely to cause the largely different PLQYs in the solution.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As revealed by photophysical experiments, complexes 2–4 show a similar deep blue emission, but their PLQYs in solution largely differ because of their largely different k nr values (Table ). Recent research work has revealed that the difference in the character of emissive triplet states can lead to largely different PLQYs for cationic Ir­(III) complexes with similar strucures . Here, complexes 1–4 all show an emission originating from 3 π–π* (C ∧ N-centered)/ 3 MLCT (Ir → C ∧ N) states, and therefore, the difference in the character of emissive triplet states is unlikely to cause the largely different PLQYs in the solution.…”
Section: Resultsmentioning
confidence: 90%
“…Recent research work has revealed that the difference in the character of emissive triplet states can lead to largely different PLQYs for cationic Ir(III) complexes with similar strucures. 57 Here, complexes 1−4 all show an emission originating from 3 π−π* (C ∧ N-centered)/ 3 MLCT (Ir → C ∧ N) states, and therefore, the difference in the character of emissive triplet states is unlikely to cause the largely different PLQYs in the solution. It has been shown that the "dark" 3 MC states in blue emissive Ir(III) complexes cause notable nonradiative decay losses.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, the electron distribution on T 1 locates throughout the chelating core of the ligand part. This result enables the complex to emit light under multiple transitional characters with numerous local excited states ( 3 MLCT py2→Pt , 3 MLCT pz→Pt , 3 LC pzpy , and 3 LC cz ), which appear to have high PLQYs. , …”
Section: Resultsmentioning
confidence: 99%
“…This result enables the complex to emit light under multiple transitional characters with numerous local excited states ( 3 MLCT py2→Pt , 3 MLCT pz→Pt , 3 LC pzpy , and 3 LC cz ), which appear to have high PLQYs. 28,32 Electroluminescent Properties. The peripheral groups with alkyl substitutions also endow the complexes with good solubility; therefore, Pt(pzpyOczpy-B1) and Pt(pzpyOczpy-B2) are suitable for solution-processed devices to evaluate the EL properties.…”
Section: Synthesis Of Pt(pzpyoczpy-b2mentioning
confidence: 99%
“…The iridium complex [(F2ppy) 2 Ir(η-Cat)] (3) exhibits rather a broad emission band at λ max = 475 nm with ϕ = 4.3 × 10 −3 and τ = 38.75 ns, which might originate from 3 LC-3 MCLT transitions (Figure 7). 46 For comparison purposes with respect to the previous work on related [(MEppy) 2 M(η-Cat)] (ME = methylester; M = Rh, Ir) 30 but containing an ester group at the pyridyl unit instead of the phenyl ring, we studied the luminescence properties of both compounds 2 and 3 in a MeOH/EtOH (1/4) mixture at room temperature and at 77 K. Unlike the iridium ester compound, which emits in the red region (λ max = 600 nm), our current compounds displayed emissions at higher energy (vide infra). It should be mentioned that the rhodium ester compound is not emissive.…”
Section: ■ Introductionmentioning
confidence: 99%